Exploring Perceptions of Deaf Persons for Recommendations towards Effective HIV/AIDS Programming in Nairobi - Shackleton, Joanna (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2009)
Purpose: To assess barriers encountered by Deaf persons from Nairobi’s informal settlements, such as language, in obtaining information and treatment services related to HIV and AIDS.Method: Upon completion of a literature review, consultation with Deaf Empowerment Kenya, two focus group discussions with Deaf community members, a quantitative questionnaire was designed and administered to 32 Deaf participants from Dandora, Haruma and Kayole.Results: Although the results from the questionnaires represent a small sample of Deaf adults in Kenya, it offers important insight into the perspectives of Deaf persons in the context of HIV and AIDS. Future programming should continue to be offered in Kenyan Sign Language (KSL), the Deaf community’s primary language - whether through seminars with interpreters and Deaf lecturers, Voluntary Counseling and Testing (VCT) HIV testing and counseling in KSL, or a new innovation: educational videos with Deaf actors. Written materials should be complementary and not the means to an end, and supplemented with clear illustrations.Conclusions: It is recommended that Deaf persons are empowered and involved in the development of learning materials to suit their unique needs, and create a sense of ownership of future education, treatment, care and support programs.